Ferric carboxymaltose in the management of iron deficiency anemia in women and men: sub-group analysis of a multi-center real-world study from India - Jaiswal, Pushpa; Gupta, Preeti; Hiremath, Bharati; Nirgund, Gayathree V.; Lalitha, R.; Kulkarni, Ketan; Tope, Rutuja; Katke, Prashant; Suryawanshi, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ferric carboxymaltose (FCM) is commonly used to treat moderate to severe anemia in India. However, real-world data on its use in the treatment of iron anemia of unspecified etiology is lacking. Methods: The real-world PROMISE study assessed the efficacy and safety of intravenous FCM in adolescents and adults with IDA across 269 centers in India. This sub-group included non-pregnant women and men with a diagnosis of anemia. Data was analysed by the study population and by severity of anemia. Results: In 555 anemia patients, there was a significant increase in Hb by 2.71 g/dl, serum ferritin by 58.6 µg/l, hematocrit, mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) (p<0.001 for all) at 4 weeks. In severe anemia patients (n=222), there was significant increase in Hb by 3.18 g/dL, serum ferritin by 55.7 µg/l, RBC count, hematocrit, MCV and MCH (p<0.001 for all) at 4 weeks. In moderate anemia patients (n=294), there was a significant increase in Hb by 2.37 g/dl and serum ferritin by 62.37µg/L (p<0.001 for both); MCV (p<0.001) and MCH (p=0.003). Only two subjects had mild anemia. No serious adverse events (SAEs) were reported. The physicians rated efficacy and safety of FCM as very good to good in 94.7% and 94.8% of subjects, respectively. Conclusions: The improvement in the hematological parameters and physicians’ clinical impression highlights that FCM can be effectively and safely used in daily clinical practice to quickly correct anemia of unknown etiology in Indian population in short span of 4 weeks.